ANALISIS SENTIMEN MASYARAKAT PADA MEDIA SOSIAL PLATFORM X TERHADAP PERTAMINA MENGGUNAKAN METODE DECISION TREE - Yksan Naibaho; Darwis Robinson Manalu; Samuel VB Manurung (Universitas Methodist Indonesia, 2026)
Platform X social media has become a platform for people to express their opinions, including on issues related to Pertamina. This study aims to analyze public sentiment on Platform X towards Pertamina using the ID3 (Iterative Dichotomiser 3) algorithm-based Decision Tree method. The data used are 2,005 tweets collected with the keyword